Upaya Peningkatan Sistem Pengelolaan Limbah Cair Terhadap Efektivitas Pengolahan Limbah Cair Rumah Sakit Umum Pusat Dokter Kariadi Semarang - Irawati, Estri; Wahyuningsih, Nur Endah; Sulistiyani, Sulistiyani (Jurnal Kesehatan Lingkungan Indonesia, 2007)
ABSTRACT Background: Generally, hospital wastewater constitutes all matter from activity in hospital, that may contain microorganisme, poisonous  and radioactive material. The aim of this research was to analyze the efforts of management system improvement to the effectiveness of  wastewater treatment of Kariadi Hospital Semarang. Method: This research was an observational research with a cross sectional approach. Data was taken by three methods: observation in the area, interview, and also from the secondary data from hospital management. The data of wastewater quality was taken as a serial data from February until March 2007 for determining the quality after the program of management system improvement. A serial data of wastewater treatment waere taken  from January, March, May, August until December 2006 Result: The  result of this research  was focused to fulfill and improve the tools for effectiveness of management  and infrastructure, involving 20 kinds of jos.  In the fact,  only 60 % or 12 kinds of jobs can be well carried out. . The result of data analysis  proved  that the efforts of management system of  wastewater improvement could  be run effectively. Meanwhile the output of its investigation showed that  temperature parameter, PH, TSS, BOD, COD, NH3-N, phosfat and E-coli concentration is still under wastewater standard  stated by the government number 10, 2004. Conclusion: SWOT analytical describes that the organization favorable for  Installation of  tools  and sanition maintance in quadran II  and for  the position of stabilisation/rasionalisation to support the turn around strategy   Key words : The waste water treatment system management, Hospital